Prevention of polymorphic light eruption by oral administration of a nutritional supplement containing lycopene, β‐carotene, and Lactobacillus johnsonii: results from a randomized, placebo‐controlled, double‐blinded study. Issue 4 (2nd January 2014) - Marini, Alessandra; Jaenicke, Thomas; Grether‐Beck, Susanne; Le Floc'h, Caroline; Cheniti, Ahsène; Piccardi, Nathalie; Krutmann, Jean
Summary Background Polymorphic light eruption (PLE) is the most common photodermatosis. Little is known about the efficacy of systemic photoprotection provided by nutritional supplements in PLE patients. Purpose The purpose of this study was to assess efficacy of nutritional supplement containing lycopene, β‐carotene, and Lactobacillus johnsonii to diminish skin lesions induced by 'photoprovocation' testing in PLE patients. Methods In this randomized, placebo‐controlled, double‐blinded study, 60 PLE patients were supplemented with the nutritional supplement or placebo. For inducing skin lesions, patient skin was exposed to single daily doses of 100 J/cm2 ultraviolet A1 (UVA1) for two consecutive days. Skin lesions were evaluated using a PLE score. Skin biopsies were taken before and after supplementation from unexposed and exposed skin, and intercellular adhesion molecule 1 (ICAM‐1) mRNA expression was assessed by real‐time polymerase chain reaction. Results Prior to supplementation, skin lesions were induced in all patients with comparable PLE scores. After 12 weeks, intake of the supplement significantly reduced the PLE score after one exposure as compared with patients taking placebo (P < 0.001). After two exposures, these differences were no longer significant. At a molecular level, the development of skin lesions was associated with an increased expression of ICAM‐1 mRNA, which was significantly reduced after supplementation (P = 0.022), but not with placebo. Conclusion The nutritional supplement provides protection against the development of UVA‐induced PLE lesions at clinical and molecular levels.